2019
DOI: 10.1111/1742-6723.13296
|View full text |Cite
|
Sign up to set email alerts
|

Review article: A primer for clinical researchers in the emergency department: Part VIII. Implementation science: An introduction

Abstract: New research findings may not lead to change in practice, or a change at the front line may be delayed by years. A number of terms have been used to describe efforts and strategies to speed a change in evidence‐based practice, such as: implementation science, knowledge translation, research translation and others. In contrast to traditional clinical research, implementation science generally aims to understand and change health professional behaviour to promote evidence uptake as opposed to attempting to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It is critical to determine how to best implement new evidence into care in non‐tertiary paediatric settings, then to evaluate effectiveness of the implementation. Important methods to determine effectiveness of knowledge translation include before‐and‐after observational studies (to determine practice prior to and after the introduction of an intervention), mixed methods research, stepped wedge study designs and cluster randomised trials, which allow the assessment of the impact of an intervention across multiple hospitals while reducing the need to obtain patient‐level data 20–22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical to determine how to best implement new evidence into care in non‐tertiary paediatric settings, then to evaluate effectiveness of the implementation. Important methods to determine effectiveness of knowledge translation include before‐and‐after observational studies (to determine practice prior to and after the introduction of an intervention), mixed methods research, stepped wedge study designs and cluster randomised trials, which allow the assessment of the impact of an intervention across multiple hospitals while reducing the need to obtain patient‐level data 20–22 …”
Section: Discussionmentioning
confidence: 99%
“…Important methods to determine effectiveness of knowledge translation include before-and-after observational studies (to determine practice prior to and after the introduction of an intervention), mixed methods research, stepped wedge study designs and cluster randomised trials, which allow the assessment of the impact of an intervention across multiple hospitals while reducing the need to obtain patient-level data. [20][21][22] The increasing use of electronic medical records provides an additional opportunity to access more than just administrative data. Analysis of large scale granular clinical data will allow us to better understand differences in local pathology, degrees of illness, socioeconomic disease determinants, practice patterns, approaches to diagnosis and management, and to identify patterns which may incorporate all of these variables in accurate predictive models.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome measures should avoid over-reliance on pain scores due to low perceived validity of the score, and variability in how scores are documented, but incorporate patient-focused measures such as ‘is your pain under control’ for staff to understand whether interventions are having a positive impact on patient experience 17. Audit and feedback have been demonstrated to be effective methods of enabling behaviour change in EDs,25 and the findings of this research indicate that audit and feedback were key tools in challenging embedded beliefs, enabling staff to understand and acknowledge poor current practice and the need for improvement. Auditing and disseminating times of assessment and provision of analgesia may enable staff to understand the impact of interventions, and how interventions may need to be adjusted or reconfigured to enable continued improvements.…”
Section: Discussionmentioning
confidence: 99%
“…CareTrack Australia found that only 57% of Australian adults received healthcare that was in line with evidence‐based guidelines 6 . Similar results were found for children, with only 60% of paediatric encounters adhering to quality care indicators for 17 conditions 7,8 . Clinicians can become entrenched in their practice and despite being aware of the evidence and wanting to change, altering clinical practice behaviour is difficult 2,4 .…”
Section: Introductionmentioning
confidence: 86%
“…Evidenced‐based practice interventions are more likely sustained if tailored to the clinicians and setting concerned 7,14,18 . A theory, model or framework to plan, evaluate and examine causal determinants of sustainability is recommended 1,25 .…”
Section: Factors Influencing Sustainabilitymentioning
confidence: 99%